Contribuições da Psicologia Escolar e Educacional para um estudo sobre as nuances da evasão em um campus universitário - Almeida, Daniela da Cunha Lopes (2022)
The psychologist’s performance in Student Assistance brought several questions about the practice of this professional in Higher Education in Brazil. One, among the numerous contributions reported by authors in the field of School and Educational Psychology, places the work of the psychologist as a possibility of intervention in the phenomenon of dropout at this level of education. In this sense, this research aimed to analyze the dropout phenomenon at the Patos de Minas campus of the Federal University of Uberlândia-MG through assumptions of School and Educational Psychology and concepts of the Historical-Cultural Psychology. For the research, with a qualitative approach, we sent an online questionnaire to all students who dropped out of campus between 2011 and 2019. Through this questionnaire, we aimed to know the history of the student’s school life – before, during and after leaving graduation – including information about the reasons involving their dropping out of the course. We had the participation of 45 former campus students, 23 female and 22 male, with 51.2% joining between 2011 and 2012. It was developed a content analysis not only of the information collected by the instrument, but also of the institutional reports available by the “Academic Administration and Control Board” (an organ of Federal University of Uberlândia), as well as the data found in the investigation of the campus implementation history. Subsequently, we developed two analytical axes: “What Psychology has to say about the phenomenon of dropout on campus: some reflections” and “The production of university dropout – from public policies to the classroom”. In the first one, when looking at the main reasons mentioned by the students, we found that School and Educational Psychology and Historical-Cultural Psychology are significant tools for a critical understanding of the causalities involved in the dropout phenomenon. On the second axis, when exploring the campus dropout numbers presented in the spreadsheet received by the institution, the different official documents and other information collected in the survey carried out through the questionnaire, we noticed the various movements made by the students during their journey in the higher education, in addition to bringing the perspective of school exclusion, which also appears to be present at this level of education. The analyzes allowed us to reflect on the complexity of reasons involved in the phenomenon, as well as the contributions of School and Educational Psychology in Student Assistance for planning and executing activities that promote learning and development, aiming at the permanence and completion of the course by the students. Thus, without intending to exhaust the theme or the possibilities of analysis raised by it, we emphasize the need for other qualitative studies about the reasons that lead to the departure of higher education students, in order to unveil and understand what is commonly called dropout in this context: a phenomenon with much more nuances than the institution supposes.